Effect of selenium supplementation on some blood biochemical parameters in male rats . - Crespo, A.M.V. (2012)
The long-term effect of selenium supplementation on blood glutathione peroxidase (GSH-Px) activity and plasma TBARS’ production (as an index of peroxidation) was evaluated in 15-mo-old male rats fed a diet supplemented with 0.25 or 0.50 ppm selenium, for 12 mo. A group of nonsupplemented age-matched rats was the control. In addition, triglycerides, phospholipids, total and free cholesterol, HDL-cholesterol, and HDL-phospholipid levels were measured in plasma. Plasma testosterone levels were also determined in order to control the aging process in these animals. The GSH-Px activity and the peroxidation level were unchanged in all the groups. However, concerning the lipid parameters, a decrease in triglycerides concentration was observed in both treated groups (p<0.05). Therefore, in these experimental conditions, despite no observed changes in parameters related to lipid peroxidation, selenium seems to be involved with triglycerides metabolism, eventually improving the triglycerides status of aged animals.